PENGAJARAN APRESIASI SASTRA DI SEKOLAH LANJUTAN ATAS KEAKRABAN GURU-MURID DENGAN KARYA SASTRA - Sugita, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
The high school is the last level in the framework of basic education, which prepares students to continue their education or to college, or to the largest number work in the society. Especially if we remember this second possibility, that possibility can not be avoided by the majority of high school graduates as a result of the state of our education today, then we should be really concerned. These concerns are not just demanding to pitch our chest, but and even more demanding of ourselves efforts to bridge the gaps between reality and expectations of education